Developing Difference: Social. Organization and the Rise of the Auto Industries of South Korea, Taiwan, Spain, and Argentina - Биггарт, Николь; Гиллен, Мауро (Journal of Economic Sociology, 2010)
All various theories of economic development (theory of modernization, interdependence, micro-systemic analysis and the theory of market reforms) suggest a core factor as the key. The followers of each of these theories claim that the countries’ development has an obstacle for their economic growth. We state that economic development does not depend on only one key factor and does not have the only one way for growth on the contrary there are several successful trajectories. Economic growth depends on how successful the country is in connecting its historical models of social organization with the world market possibilities. This paper is devoted to the sociological theory cross-countries comparative advantages, which takes into account not only the influence of the economic factors but institutional models of power relations. Such models legitimize the actors and specific relations between them, and in some spheres this counts for the successful development and in other spheres it does not. The given approach is supported by the comparative analysis of rather difficult processes of automobile industry development in South Korea, Taiwan, Spain and Argentina.